PENDIDIKAN PONDOK PESANTREN TAHFIZUL QUR’AN DALAM UPAYA PEMBERDAYAAN HAFIZ-HAFIZOH QORI-QORIAH - Sumarto Sumarto (AT-TAJDID, 2017)
A directed educational process will bring this nation to a better civilization. Conversely, the education process that is not directed, will only consume time, effort, and funds without any results. Thus, the education system as the implementation of national education greatly determines the progress of the decline of this nation. The educational program of memorizing the Qur'an is a program of memorizing the Qur'an with mutqin (strong memorization) of the lafadz-lafadz of the Qur'an and memorizing its meaning strongly which makes it easy to present it every time facing various problems of life, because al- The Qur'an always exists and lives in the heart all the time, making it easier to apply and practice it. Memorizing the Qur'an is not an easy, simple, and can be done by most people without taking special time, sincerity to mobilize abilities and seriousness, because memorizing the Qur'an is a very grand and great task. No one is able to do it other than Ulul mi Azmi, which is a person who is determined and rounded and wants to work. This is because there are many problems that must be faced by the memorizers of the Qur'an to achieve a high degree in the sight of Allah SWT. Starting from the development of interest, creation of the environment, division of time to the method of memorization itself. Many memorizers of the Qur'an also complain that memorizing is difficult. This is due to disorders, both psychiatric disorders and environmental disorders.